Potent Antimicrobial Azoles: Synthesis, In Vitro and In Silico Study - Zeynep Özdemir; Yaren Nur Zenni; Arzu Karakurt; Suat Sari; Selma Saraç; Mevlüt Akdağ; İrem Bozbey Merde; Didem Kart; Roberto Venanzoni; Giancarlo Angeles Flores; Paola Angelini; Muzammil Kabier; et al. (MDPI AG, 2024)
Background/Objectives: The increase in fungal infections, both systemic and invasive, is a major source of morbidity and mortality, particularly among immunocompromised people such as cancer patients and organ transplant recipients. Because of their strong therapeutic activity and excellent safety profiles, azole antifungals are currently the most extensively used systemic antifungal drugs. Antibacterial properties of various topical antifungals, such as oxiconazole, which features oxime ether functionality, were discovered, indicating an exciting prospect in antimicrobial chemotherapy. Methods: In this study, eleven new oxime ether derivatives with the azole scaffold (5a-k) were synthesized and tested for their antimicrobial effects using the microdilution method to obtain broad-spectrum hits. Results: Although the title compounds showed limited efficacy against Candida species, they proved highly effective against dermatophytes. Compounds 5c and 5h were the most potent derivatives against Trichophyton mentagrophytes and Arthroderma quadrifidum, with minimum inhibitory concentration (MIC) values lower than those of the reference drug, griseofulvin. The MIC of 5c and 5h were 0.491 μg/mL and 0.619 μg/mL against T. mentagrophytes (MIC of griseofulvin: 2.52 μg/mL). The compounds were also tested against Gram-positive and Gram-negative bacteria. Briefly, 5c was the most active against Escherichia coli and Bacillus subtilis, with MIC values much better than that of ciprofloxacin (MIC of 5c = 1.56 μg/mL and 1.23 μg/mL, MIC of ciprofloxacin = 31.49 and 125.99 μg/mL, respectively). Molecular docking suggested a good fit in the active site of fungal lanosterol 14α-demethylase (CYP51) and bacterial FtsZ (Filamenting temperature-sensitive mutant Z) protein. Conclusions: As a result, the title compounds emerged as promising entities with broad antifungal and antibacterial effects, highlighting the utility of oxime ether function in the azole scaffold.